Analisis Biaya Pendidikan dan Kondisi Sosial Ekonomi Orang Tua terhadap Keputusan Siswa Memilih Sekolah di SMP Negeri 1 Karangrejo Tahun Ajaran 2017/2018 - Nafik Umurul Hadi, Tri Kresna Murti (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
Karangrejo 1 Public Middle School shows that there are problems in decision making carried out by prospective students to continue their education in Karangrejo 1 Middle School. This study aims to analyze: the partial and simultaneous influence of education costs on parents' socio- economic conditions on the decision of students to choose schools in Karangrejo 1 Public Middle School 2017/2018 academic year Descriptive method with a quantitative approach. The data analysis technique used is multiple linear regression analysis. Based on the results of the study show that: (1) there is a significant influence between the cost of education on the decisions of students choosing schools in Karangrejo 1 Public Middle School with a tcount of X1 Against Y worth tcount (3.693)> t table (1.987). (2) there is an influence there is a significant influence between the socio-economic conditions of parents on the decision of students to choose schools in Karangrejo 1 Public Middle School with a tcount of X1 Against Y worth tcount (3.352)> ttable (1.987). (3) there is an influence there is a significant influence between the cost of education and the socio-economic conditions of parents on the decision of students to choose schools in SMP 1 Karangrejo with a tcount of X1 Against Y worth tcount (3.352)> ttable (1.987).